Community health agents: your quality of life and your occupational risks (Research, Society and Development, 2020)
Aim: To assess the occupational risk generated by the work activity of Community Health Agents (CHA's) in the municipality of Olinda / PE. Method: This is a descriptive, cross-sectional study. It was developed in two Basic Health Units in Olinda, with the CHA’s professionals totaling a sample of 29 individuals. Initially, participants signed the Informed Consent Form and then a sociodemographic data sheet, ergonomics census, Couto checklists and Rapid Upper Limb Assessment (RULA) were applied. Results: Most of them were female (82.7%), with a mean age of 49.1 ± 8.4 years and an average working time of 16.2 ± 5.9 years. With the ergonomics census it was identified that 75.9% have work-related pain. There was a negative correlation between the RULA and the column checklist, and between the column and the job checklist; and a positive correlation between RULA and job. Conclusion: CHA's may develop musculoskeletal disorders in the future due to prolonged postures and long walks that are carried out with inadequate bags. In addition, the position of these agents does not have a good ergonomic condition, making an immediate change necessary for these injuries to be mitigated.